2013
DOI: 10.1111/iej.12075
|View full text |Cite
|
Sign up to set email alerts
|

CBCT for the assessment of second mesiobuccal (MB2) canals in maxillary molar teeth: effect of voxel size and presence of root filling

Abstract: CBCT was associated with higher mean values of specificity and sensibility than radiographic examination for the detection of MB2 canals. When endodontic retreatment is necessary removal of the root filling prior to the CBCT examination eliminates artefacts, thereby permitting the use of the 0.3-mm voxel protocol that has good diagnostic performance and lower radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 35 publications
(74 reference statements)
5
85
0
8
Order By: Relevance
“…In-vivo vertical VRF that could not be visualized on PA radiographs were diagnosed with CBCT [20]. Mesiolingual canals of maxillary molars (MB2) were detected with higher specificity and sensitivity using CBCT than PA radiograph [21]. Not surprisingly, one study found that additional information obtained from CBCT led endodontists to modify their treatment plan in approximately 62% of the cases [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In-vivo vertical VRF that could not be visualized on PA radiographs were diagnosed with CBCT [20]. Mesiolingual canals of maxillary molars (MB2) were detected with higher specificity and sensitivity using CBCT than PA radiograph [21]. Not surprisingly, one study found that additional information obtained from CBCT led endodontists to modify their treatment plan in approximately 62% of the cases [22].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of artifacts caused by root canal filling materials resulted in inaccuracies of VRF and MB2 detection by CBCT [21] [25]. It is recommended that when endodontic retreatment is necessary to remove the root filling prior to the CBCT examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been used to evaluate RCS, which could assess the risk of tearing and perforation at the furcation area, such as histological sections 9 , serial sections 10 , clearing 11 , scanning electron microscopy 12 , stereomicroscope 13 , radiographs 14 , silicone impressions of the root canal 15 , CBCT 16,17 , and micro computed tomography (micro--CT) 18 . Among clinical methods, which can be used in vivo, CBCT is a promising one, since it allows tridimensional evaluation 19,20 . For in vitro studies, both micro-CT and stereomicroscope images are used for gold standard references in RCS evaluations [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad, los avances tecnológicos permiten contar con el apoyo de las tomografías computarizadas de haz de cono (CBCT, por su sigla en inglés de cone beam computed tomography) (7)(8)(9)(10)(11), que muestran un alto grado de precisión al proporcionar información anatómica en todos los planos del espacio y facilitar la identificación de conductos radiculares (12)(13)(14). Las CBCT han cobrado gran relevancia, debido a la fuerte correlación entre los datos adquiridos mediante CBCT y los de histología (13).…”
Section: Introductionunclassified